Metal trace elements in mussels in Urubuqueçaba Island, Santos Bay, Brazil - Campolim, Marcos Bührer; Henriques, Marcelo Barbosa; Petesse, Maria Letizia; Rezende, Karina Fernandes Oliveira; Barbieri, Edison (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to verify the existence of bioaccumulation in mussels of the species Perna perna, by determining the concentration of metal trace elements, in Urubuqueçaba Island, Santos Bay, Santos, SP, Brazil. Mussels were collected in natural banks and rocky shores, and sampling took place from April 2010 to June 2011. The concentration of the trace metal elements – aluminum, cadmium, cromium, copper, iron, manganese, nickel, lead, and zinc – was determined according to mussel sex, length, and seasonality classes, in a flame atomic absorption spectrometer. Statistical analyses were applied to the results with the use of the software PAST, with parametric and nonparametric approaches, at 5% probability. In the summer, mussels show the highest concentrations of cadmium, copper, lead, and zinc. Females of P. perna concentrate more copper; for the other elements, there are no significant differences between sexes. The length classes with the highest concentrations are 3.5–5.5 cm for Al and Fe, and 6.5–8.5 cm for Cr.